PENGARUH PEMBERIAN EKSTRAK BAWANG PUTIH TERHADAP MORTALITAS KEONG MAS - Alfian Rusdy (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2010)
The objective of the research was to study effectiveness of garlic extract (Allium sativum) at various concentrations to control golden snails (Pomacea Canaliculata). The experiment was conducted in Agriculture Faculty, Iskandar Muda University, Banda Aceh. The experiment applied a completely randomized design (CRD) with 5 replicates. Factors evaluated were various concentrations of garlic extract, consisting of 4 levels, i.e. 5 percent, 10 percent, 15 percent, and 20 percent of water. Variables observed were eating activity, mortality, and rate of death. Result showed that eating activity, mortality, and rate of death were significantly affected by concentrations of garlic extract.